1987
DOI: 10.1111/j.1365-2559.1987.tb01854.x
|View full text |Cite
|
Sign up to set email alerts
|

A histological and immunocytochemical study of lymphoid tissue in rectal biopsies from homosexual men

Abstract: A histological study of the lymphoid tissue of the rectums of 323 homosexual and 30 heterosexual men (including five intravenous drug users seropositive for human immunodeficiency virus, HIV) was undertaken. Marked lymphoid hyperplasia (germinal centre greater than 680 microns in diameter) was found in 13 men, nine of whom had a sexually transmitted infection of the rectum. Immunocytochemical studies showed that the germinal centres contained B-cells and follicular dendritic cells, surrounded by CD4+ and CD8+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This practice has only recently been introduced, principally as a result of the emergence of LGV proctitis based on the genovar L of LGV. Although the majority of men with rectal infection with the genotype trachomatis are symptomless,15 inflammatory changes that may increase the risk of HIV transmission can be identified 16. There is also the possibility of transmission of chlamydiae to the urethra of the sexual partner, therefore the identification and treatment of infected individuals may be justified.…”
Section: Discussionmentioning
confidence: 99%
“…This practice has only recently been introduced, principally as a result of the emergence of LGV proctitis based on the genovar L of LGV. Although the majority of men with rectal infection with the genotype trachomatis are symptomless,15 inflammatory changes that may increase the risk of HIV transmission can be identified 16. There is also the possibility of transmission of chlamydiae to the urethra of the sexual partner, therefore the identification and treatment of infected individuals may be justified.…”
Section: Discussionmentioning
confidence: 99%
“…In the years following the identification of AIDS, prompted partly by the high frequency of enteropathies in PWH (73), histological studies identified a loss of CD4 + T cells in gastrointestinal biopsies of PWH (74)(75)(76)(77)(78)(79). Lim and colleagues also proved that, similar to circulation, memory CD4 + T cells were the preferentially depleted cell subset in the gut during HIV infection (80).…”
Section: Gastrointestinal (Gi) Tractmentioning
confidence: 99%